Creación de un recorrido virtual 3D del Complejo Arqueológico Ingapirca - Coronel Cevallos, César Marcelo (2018)
The development of tourism in Ecuador in the last decades, has been one of the main pillars that foment the creation of new jobs and an increment to the economy of the country. However, it has only centered specifically on on-site and ecological tourism. The development of new technologies, means of communication and tools that allow the creation of virtual environments opens a new field for the diffusion of these projects on digital platforms. These are used everyday by millions of people around the world, and allow them to reach different places and provide a closer experience that motivates the users to visit them first-hand. For this reason, the creation of the virtual tour of Ingapirca allows to promote different historical sites of Ecuador, with their corresponding cultural diversity and history. All this, using an interactive project that allows an enormous amount of users around the world to access this enriching experience.